Optimization of Higher Education Internal Quality Audits Based on Artificial Intelligence - Elviwani; Buaton, Relita; Muhammad, Zarlis; Dilham, Ami (Yayasan Kita Menulis, 2022)
Internal Quality Audit is an independent and documented systematic testing process to ensure that the implementation of activities in higher education is in accordance with the procedures and the results are in accordance with the standards to achieve the goals of the institution. Quality can be guaranteed by ensuring that each individual has the skills he needs to do the job properly. Quality orientation in development life in Indonesia is something that is very urgent, must be supported and developed in order to respond to the trend of global competition. There are significant differences in the accreditation and quality assurance system with the previous version, it is necessary to develop a strategy by building an artificial intelligence-based system. The method used is to build an online system by involving experts and assessors to develop concepts in accordance with the points of the 9 criteria accreditation forms, to build a digital quality audit form for matching and the level of conformity between the implementation of higher education standards and the standards set, the benefit is to help universities implement digital and intelligent based internal quality audits, know the tri dharma standards of higher education that must be improved, maintained and deviated